Tuberculous mycobacteria bacilli fluorescence and compare with Ziehl- Neelsen stain in fine-needle aspiration cytology of tubercular lymphnode - Krishna, Mani; Kumar, Adesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: Tuberculosis is infectious disease caused by Mycobacterium tuberculosis. There are various methods for diagnosis of tuberculosis such as direct clinical material examination of tubercular bacilli by Ziehl – Neelsen (ZN) staining, demonstration of tubercular bacilli by auramine – rhodamine (AR) staining and autofluorescence (AF). Methods: Present study was done clinically suspected tubercular patients. All received samples Zn stain, fluorescent stain and PAP stain were applied. Results: Among the clinically suspected patients 88 was diagnosed with tuberculosis. Female preponderance was noted accounting for 60.23% (53/88) of cases. Of the 88 aspirates, the smear positivity for acid fast bacilli (AFB) on the ZN method was 37.5% (33/88) while the positivity increased to 81.82% (72/88) on the AR fluorescent method and 86.36% (76/88) on AF. Conclusions: AF staining is more sensitive than the auramine – rhodamine fluorescent and ZN staining in demonstration of mycobacterium bacilli in fine needle aspiration cytology of tubercular lymphnode.